Вироби із заліза класичного часу з приміських садиб Ольвії - Папанова, В.А.; Ляшко, С.М. (Археологія, 2018)
Статтю присвячено виробам із заліза класичного часу із приміських садиб Ольвії Широка балка 6 та Широка балка 7. До наукового обігу вводяться предмети, які знайдені на двох приміських садибах, а також із поховань сімейної ділянки ойкоса. Аналіз знахідок дозволяє зробити висновки щодо економіки, соціального статусу та повсякденного життя населення двох приміських ольвійських садиб. The article introduces iron objects excavated at the Shyroka Balka 6 (οικος — oikos) dated by the end of the 6th — the 30-ies of the 4th century BCE and at the Shyroka Balka 7 (χωριον — chorion) — the second third of the 5th — the beginning of the 3rd centuries BCE, as well as from the area of family burials of the oikos graves. They are introduced by tools and household items such as nails, door bolts, chain links, a needle, a horse harness ring, knives, a fishing hook, a sickle, staples and a strigil. The strigil is of a particular interest. Only free citizens could do sports in the ancient world. We can assume that the inhabitants of the oikos were the full status Olbian citizens and therefore could attend the gymnasium of Olbia. The complex of iron objects from two suburban estates is relatively homogeneous and close to the similar objects of Olbia from the chora settlements of the Classical period. Despite its scarcity, the iron objects are of special interest too, because they allow reconstructing the life, the work and crafts, namely, to clarify the conclusions about the persiut of suburban estates inhabitants. В статье вводятся в научный оборот предметы из железа, раскопаные на усадьбах Широкая балка 6 (ойкос) конца V — 30-х годов IV вв. до н. э. и Широкая балка 7 (хорион) второй трети V — начала III вв. до н. э., а также из погребений семейного участка захоронений ойкоса. Они представлены орудиями труда и хозяйственно-бытовыми предметами: гвозди, дверной засов, звенья цепи, игла, кольцо от конской упряжи, ножи, рыболовный крючок, серп, скобы, стригиль и др. Отметим крайне редкую находку стригиля. В античном мире спортом могли заниматься только свободные граждане. Поэтому можно предположить, что жители ойкоса были полноправными ольвийскими гражданами и поэтому могли посещать гимнасий Ольвии. Комплекс железных изделий из двух пригородных усадеб относительно однороден и близок аналогичным предметам Ольвии и поселений ее хоры классического времени. Однако, несмотря на немногочисленность, железные изделия вызывают особый интерес, т. к. они позволяют реконструировать быт, занятия и ремесла. В частности, уточнить выводы о занятии жителей этих усадеб.